2017
DOI: 10.1177/0884533617728487
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Analysis–Derived Measurements in Chronic Hepatitis C: Clinical Relevance of Fat‐Free Mass and Phase Angle Evaluation

Abstract: Objective: Because cirrhotic patients are at high risk of malnutrition and sarcopenia, we evaluated the prevalence of low fat‐free mass index (FFMI) and low phase angle (PhA) among patients with chronic hepatitis C (CHC). Methods: In total, 135 subjects with CHC (50.4% males; mean age, 52.4 ± 11.8 years; 65.9% noncirrhotic and 34.1% compensated cirrhotic patients) were prospectively included and evaluated by bioelectrical impedance analysis. Subjective global assessment was used to evaluate malnutrition. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
(91 reference statements)
0
11
0
1
Order By: Relevance
“…In addition, PhA values might be altered in subjects with severe obesity due not only to changes in BCM but also to those in tissue hydration, which occur because of a physiologically higher ECW/TBW ratio in adipose tissue or a pathophysiological fluid overload [18]. Of note, in terms of body function PhA has been directly related to muscle strength [15,19], being higher in athletes [20] and lower in sarcopenic subjects [21], to impaired quality of life [22] and poor prognosis in various chronic diseases [23,24]. Thus, based on the aforementioned points, the EWGSOP 2019 consensus on sarcopenia proposed PhA as a possible index of muscle quality [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PhA values might be altered in subjects with severe obesity due not only to changes in BCM but also to those in tissue hydration, which occur because of a physiologically higher ECW/TBW ratio in adipose tissue or a pathophysiological fluid overload [18]. Of note, in terms of body function PhA has been directly related to muscle strength [15,19], being higher in athletes [20] and lower in sarcopenic subjects [21], to impaired quality of life [22] and poor prognosis in various chronic diseases [23,24]. Thus, based on the aforementioned points, the EWGSOP 2019 consensus on sarcopenia proposed PhA as a possible index of muscle quality [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed a statistically significant difference of a lower PA in patients with cirrhosis. This low PA was linked to malnutrition (23) . Dorna et al also demonstrated the association between PA and advanced fibrosis in HCV patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Bering et al examined 135 patients (68 men and 67 women) with hepatitis C. They studied the nutritional status of patients using the Subjective Global Assessment (SGA) scale for the risk of developing cirrhosis. A low PA value was associated with high risk of developing liver cirrhosis (OR = 3.92, p < 0.01) and high risk of malnutrition (OR = 5.52, p = 0.05) [35].…”
Section: Discussionmentioning
confidence: 99%